2011
DOI: 10.1002/path.2986
|View full text |Cite
|
Sign up to set email alerts
|

The retinoid signalling molecule, TRIM16, is repressed during squamous cell carcinoma skin carcinogenesis in vivo and reduces skin cancer cell migration in vitro

Abstract: Retinoid therapy is used for chemo-prevention in immuno-suppressed patients at high risk of developing skin cancer. The retinoid signalling molecule, tripartite motif protein 16 (TRIM16), is a regulator of keratinocyte differentiation and a tumour suppressor in retinoid-sensitive neuroblastoma. We sought to determine the role of TRIM16 in skin squamous cell carcinoma (SCC) pathogenesis. We have shown that TRIM16 expression was markedly reduced during the histological progression from normal skin to actinic ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 28 publications
1
27
1
4
Order By: Relevance
“…The C-terminus of TRIM16 contains an RFP-like or B30.2/SPRY (B30.2) domain. TRIM16 expression is induced in different types of cancer, when the cancer cell is forced to proceed down a differentiation pathway (12,13,24,25); however, the role of TRIM16 in prostate cancer has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminus of TRIM16 contains an RFP-like or B30.2/SPRY (B30.2) domain. TRIM16 expression is induced in different types of cancer, when the cancer cell is forced to proceed down a differentiation pathway (12,13,24,25); however, the role of TRIM16 in prostate cancer has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Given the connections to autophagic machinery via TRIM16, the role of Galectin-3 in control of bacteria or pathology associated with mycobacterial infection can now be mechanistically linked to the TRIM-driven process of precision autophagy (Kimura et al, 2016), which differs from bulk autophagy. TRIM16 is also known as estrogen-responsive B box protein, and its role in cancer (a general property of TRIMs (Hatakeyama, 2011)) has been linked to specific effects on immune signaling (Sutton et al, 2014), cell survival (Kim et al, 2013), cell migration and metastasis (Marshall et al, 2010; Sutton et al, 2014) through various mechanisms, including measures of membrane repair (Cheung et al, 2012; Marshall et al, 2010), with the latter potentially overlapping with the processes described in this work.…”
Section: Discussionmentioning
confidence: 86%
“…TRIM16 is a ubiquitously expressed, predominately cytoplasmic protein, with mRNA expression levels highest in the embryonic brain and in adult testes 3 . We have previously demonstrated that overexpression of TRIM16 causes decreased proliferation in neuroblastoma and in lung, breast and skin cancer cell lines 4 - 7 . Overexpression of TRIM16 is able to enhance retinoid-induced differentiation and causes downregulation of cell cycle factors E2F1 and pRB.…”
Section: Introductionmentioning
confidence: 99%